Effect of IAA on coumarins synthesis in Angelica dahurica under soil compactness stress - Xinglong Zhu; Xiaoyan Chen; Chengfeng Huang; Yongfeng Zhou; Tao Zhou; Qinghua Wu; Jin Pei (Scientific Reports, 2025)
Abstract Angelica dahurica (Hoffm.) Benth. & Hook.f. ex Franch. & Sav (A. dahurica) is widely used in food, medicine and other applications due to its rich content of starch and secondary metabolites and is grown on a large scale in southwestern and northern China, where it is one of the commonly used traditional Chinese medicines(TCM). Modern studies have pointed out that the effect of soil compactness on plant root development as well as secondary metabolite synthesis is extremely significant, and auxin may play an important role in this process. However, the effect of soil compactness on coumarins synthesis in A. dahurica and the reasons for the changes in coumarins content are unknown in the current actual cultivation, which is extremely unfavorable for A. dahurica, which is dependent on the content of secondary metabolites. In this study, A. dahurica was planted in soil environments with low (5 kPa), medium (15 kPa) and high (25 kPa) soil compactness and harvested at 80, 100 and 120 d, respectively. The plant development process was quantified and the indole-3-acetic acid(IAA) content of the corresponding root tips and the total coumarins content of the primary and lateral roots were examined. We aimed to (i) clarify the effects and patterns of soil compactness on the morphology and coumarins synthesis of A. dahurica, and (ii) explore the effects of IAA on coumarins synthesis in the roots of A. dahurica in response to soil compactness stress. It was found that both too low and too high soil compactness resulted in low biomass accumulation of A. dahurica, but the latter showed a higher rate of coumarins accumulation. IAA was positively correlated (p < 0.1) with various morphological parameters and total coumarins content, suggesting that IAA may be associated with coumarins synthesis. Thereafter, we confirmed through validation experiments that IAA positively regulates coumarins synthesis in the roots of A. dahurica, and that it is intrinsic to the positive correlation between root morphology parameters and total coumarins content (p < 0.001) in A. dahurica. The results of the study showed that in response to soil compactness stress, the root system of A. dahurica regulates root morphology by secreting IAA to resist soil compactness stress, while at the same time IAA stimulates the signaling pathway for coumarins biosynthesis. This study has significant practical implications for the cultivation and quality improvement of A. dahurica.